Can the reduced level of alveolar bone in the initial stages of juvenile periodontitis anterior to the first molar be explained as arrest in alveolar bone growth? - Inger Kjaer (Wolters Kluwer Medknow Publications, 2013)
Introduction : It is generally agreed that juvenile periodontitis is more likely caused by genetic factors than environmental/bacterial factors. Until now, all research reports focus on alveolar bone destruction as a characteristic symptom. This is questioned in the present study. The Hypothesis : It is hypothesized that initial so-called bone loss in juvenile periodontitis can be explained as arrest in alveolar bone apposition during alveolar growth. Therefore, the purposes of this study are to analyze the morphology of cortical bone at the alveolar process located between the second premolar and first molar and to analyze whether the time of occurrence of juvenile periodontitis coincides with the time of the body growth spurt maximum of the individual. Orthopantomograms and dental films from 29 patients diagnosed with juvenile periodontitis were analyzed. Visual assessment of cortical bone on the alveolar process anterior to the first molar was performed. In addition, skeletal hand maturation was scored on hand radiographs from five patients and the maturity was related to body height. The results showed that in 18 patients the alveolar bone had a distinct compact with a normal level compared to the enamel cementum border of the second premolar and a pathological deep level compared to the enamel cementum border of the first molar. This abnormal alveolar bone level was first diagnosed shortly after pubertal maximum. Furthermore, 11 patients had uneven, indistinct alveolar cortical bone with the same abnormal level compared to the column of the second premolar and first molar. Evaluation of the Hypothesis: As a conclusion, it is evaluated that patients in the early stage of juvenile periodontitis have a bone loss due to arrest in alveolar bone growth anterior to the first molars during the early stage of the disease. Thereafter, the destruction of the cortical bone occurs.